How to Measure and Manage Perceived Quality of Higher Education by International Degree Students at Two Case Universities in Finland - Jogunola, Olatunde; Varis, Keijo (Journal of Management Policy and Practice, 2019)
The study deals with the quality of higher education and the policy of measuring it from the point of view of the students’ and educational institutions' external reputation. The results of the study will help to better manage and develop universities in the future. The study is limited to the two universities used as a case study, and to past and present students of their international master’s degree programs. The sample size of the research was limited. In the student experience survey, the work did not consider factors such as the effect of number of semesters, the education success, level of students or the students’ study programs in the perceived educational quality of the services. Therefore, the findings cannot be used to generalize about the educational quality of all Finnish universities. The research’s findings and suggestions should help university administrators and relevant government agencies to develop strategies to improve student experience now as Finland has taken into use tuition fees for non-EU/EEA students. Furthermore, the student experience survey introduced in this research is a valuable tool, which can be used in benchmarking universities in Finland so that the public can have information to make judgements about the perceived level of quality of the educational services of each university. Researchers suggest that all universities and universities of applied sciences should make regular use of the survey. This will ensure that Finnish universities and universities of applied sciences will have a favorable education environment, which would lead to improved global brand image.